Formulasi Pembuatan Edible Spoon Dengan Penambahan Varian Ekstrak Pewarna Alami Serta Bubuk Kayu Manis (Cinamomum Burmanii) Sebagai Anti Mikroba - Puja Arismawanti; Irmayanti Irmayanti; Chairuni AR Chairuni AR (Serambi Journal of Agricultural Technology, 2021)
Edible spoon is one kind of edible cutlery, which is a disposable meal made of biodegradable materials so that it can reduce the neighborhood use of inhospitable plastic diets. Natural dyeing is safer than synthetic dyes. For example (leaves of pandan, carrots and purple sweet potatoes. The purpose of the study is identify the effects of adding a natural pigment extract, adding cinnamon powder and an interaction between a natural dye extract and cinnamon powder as anti microbial against edible spoon. The study uses a full random design (RAL) prosecuting patterns of 3 levels with 2 factors. The factor I is a natural dye extract with three levels of it: P1 = extract of pandan leaves (3%), P2 = carrot extract (3%) and P3 = extract of purple sweet potato (3%). The factor II is cinnamon powder with 3 levels of yatiu K1 =1%, K2 =1.5% and K3 =2%.  The parameters analyzed in the study are for tests of water levels and hedonic organoleptic tests (color, taste and aroma). Studies have shown that the effects of adding a variant extracted from natural dyes have a very real impact on water levels, hedonic organoleptic tests (colors and scents), but have no real effect on hedonic organoleptic tests. The effect of cinnamon powder is particularly evident on water levels tests, hedonic organoleptic tests (color and taste), but it has no real effect on scent hedonic organoleptic tests. Whereas the mixing of variant extracts of natural dyes and cinnamon powders does not make a real difference in water levels, organoleptic tests (color, taste and aroma). The best treatment based on adding extract of pandan leaves and cinnamon powder 2% (P1K3) is edible spoon with the chemical properties of water 9.90%, hedonic organoleptic {color 1.87 (not like), 4.58 (likes) and scent 4.40 (likes)}.